Association between relative fat mass and cardiovascular disease: a cross sectional study based on NHANES - Zhang, Bin; Zhu, Changguo; Ma, Lanhua; Shen, Bai; Zhang, Gaoxing (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiovascular disease (CVD) represent a primary factor contributing to death worldwide. Conventional indicators of obesity, waist circumference, waist-to-hip ratio, body mass index (BMI), have limitations in differentiating between fat and muscle mass. Relative fat mass (RFM), a novel metric based on waist to height ratio, has been proposed as a more accurate measure of total body fat percentage. This research examines the relationship between RFM and CVD, utilizing data sourced from the National Health and Nutrition Examination Survey (NHANES).MethodsThis cross sectional study utilized data sourced from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. Participants with unavailable data on waist circumference, height, CVD complications, or total cholesterol were excluded. A total of 45,000 participants were included and divided into quartiles based on RFM values. Multivariate logistic regression models were used to assess the association between RFM and CVD. Moreover, analyses including subgroup evaluations, smooth curve modeling, and testing for interactions were conducted.ResultsThe prevalence of CVD was 10.42% (4,691) among the 45,000 participants. Fully adjusted models showed a significant positive association between RFM and CVD (OR = 1.04; 95% CI = 1.03–1.05; P < 0.001). Participants in the highest RFM quartile(Q4) had a 2.11 fold increased risk of CVD compared to those in the lowest quartile (OR = 2.11; 95% CI = 1.76–2.53; P < 0.001). Subgroup analyses indicated that the association was stronger in individuals aged <60 years, nonHispanic Whites, and those with BMI < 30 kg/m2.ConclusionsElevated RFM is associated with an higher proportion of patients with CVD, suggesting that RFM may be a valuable indicator for CVD prevention and management. Future prospective studies are warranted to further explore the causal relationship between RFM and CVD.